Khatmil Qur’an Bil Ghaib Sembilan Khataman (Studi living Alquran dalam Buka Luwur Kangjeng Sunan Kudus) - Albab, Hasan (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2021)
Sunan Kudus is one of the walisongo figures who got the nickname of waliyy al'-ilmi he is also called as founding father of Kudus City, therefore the people in Kudus every year commemorate the day of his death in the opening luwur(grave) event. Andone of the agenda  is khatmil Qur'an bil ghaib 9 khataman (reciting all pages of Qur’an based on memorizing nine times). In the implementation of every khataman is read by two people so that the number is eighteen people for nine khataman. The number nine is chosen because it has many meanings, such as the number of sub-districts in Kudus, the number of Walisongo as well as the number of stars in the Nahdlatul Ulama symbol. The main purpose of this event is to send prayers to Sunan Kudus although in next time founded other many purpose.